DIFFERENT ENDURANCE CHARACTERISTICS OF FEMALE AND MALE GERMAN SOCCER PLAYERS - Baumgart, C. (Institute of Sport in Warsaw, 2014)
The aims of the present study were to assess gender differences regarding lactate threshold and intermittent shuttle run performance in female and male soccer players as well as to investigate the relationships between both endurance characteristics in both genders. Fourteen female (1(st) division) and thirteen male (4(th) division) soccer players completed an incremental test (IT) to determine running velocities at 2 and 4 mmol · l(−1) blood lactate (v2 and v4) and maximum velocity (v(max)) as well as an interval shuttle run test (ISRT) to determine running distance. Based on v2 and v4 and their percentages in relation to v(max), three intensity zones were calculated: a low lactate zone (<v2), a lactate accommodation zone (v2 to v4), and a lactate accumulation zone (>v4). Female soccer players have a lower v4 (8.2%), v(max) (11.3%) and ISRT distance (31.6%). No gender difference was found in v2. In contrast to males, ISRT distance correlates with v(max) as well as with v2 and v4 in female soccer players. The intensity zones <v2 and >v4 differ between genders. The present study revealed that gender differences increase when the running performance is intermittent including change of directions. In both genders, different relationships between lactate threshold and intermittent shuttle run performance exist. During incremental testing, the running performances of female and male players reflect different distributions of aerobic and anaerobic metabolic pathways. The revealed gender differences should be considered for soccer endurance training.